Exploring the experiential meanings of the COVID-19 survivors' expressions - Zulprianto Zulprianto; Rebecca Fanany (Universitas Syiah Kuala, 2023)
Language transforms experience into meaning. Grammar, which can be metaphorically construed as its powerhouse, enables such a transformation. One of the linguistic approaches utilised to understand the linkage between the semiotic and material world is Systemic Functional Linguistics (SFL). SFL argues that the experiential meaning of a clause can be investigated through its transitivity structures in terms of Process, Participant, and Circumstance. This study carries out a transitivity analysis of expressions shared by COVID-19 survivors from different parts of the world in an attempt to learn how they construe their experience of illness. The data were obtained from online newspapers published in different countries and conveniently developed into a corpus from which COVID-19 survivors' expressions were extracted. All texts under examination were reported in English regardless of their original language. This study examines the survivors' direct expressions through their transitivity structures using the SFL framework. The results show that these individuals frequently used relational and abstract material Processes in describing their illness, meaning that they tended to express their physical or psychological experiences metaphorically as beings and actions. This suggests that they abstractly construe their experiences with this viral disease. Constructing experiences abstractly is likely driven by the need to distance themselves from experience as a way of coping with an event perceived as potentially life-threatening.